Inflammatory myofibroblastic tumours of the duodenopancreaticobiliary tract - Shah, Pritik A (BMJ Case Rep, 2021)
Inflammatory myofibroblastic tumours (IMTs) are rare benign neoplasms of intermediate malignant potential that are found in the lungs and rarely at extrapulmonary sites common in children and young adults. IMTs tend to be locally invasive and have some amount of metastatic potential as well. We present two cases of IMTs involving the duodenum, pancreas and distal bile duct. The first case presented with extensive involvement of the first three parts of the duodenum and head of the pancreas, while the second presented with a pancreatic and biliary tree involvement. Upon examinations and investigations, these tumours mimicked malignant neoplasms. A Whipple procedure for surgical resection was undertaken in both cases. The histological findings showed fascicles of spindle cells with infiltration of lymphocytes and plasma cells. The inflammatory myofibroblastic tumour was diagnosed based on pathological grounds with immunohistochemistry. Preoperative diagnosis of IMTs is difficult and complete surgical resection is the primary treatment.